Skutar I.D., Yurchenko I.V., Yurchenko O.I. Hybrid System For Analysis And Forecasting Of Financial Asset Dynamics Based On Stochastic Differential Equations And Recurrent Neural Networks // Scientific World Journal.– 2026.– Issue №36, Part 2.– P.152–164.– Published by Academy of Economics named after D.A. Tsenov, Bulgaria (jointly with SWorld). - Юрченко, Ігор Валерійович; Юрченко, Олег Ігорович; Скутар, Ігор Дмитрович (Published by Academy of Economics named after D.A. Tsenov, Bulgaria (jointly with SWorld)., 2026)
This article addresses the problem of developing hybrid information-analytical systems for financial markets capable of operating in real-time. It proposes the architecture of a web-based application that integrates classical stochastic calculus models (Geometric Brownian Motion and the Vasicek model) with deep learning algorithms (LSTM recurrent neural networks). The study describes the mathematical framework, numerical discretization methods (Euler-Maruyama scheme), and market noise generation techniques (Box-Muller transform). The choice of the technology stack (React.js, WebSocket) and streaming data management algorithms (sliding window) is justified. Finally, an analysis of the obtained simulation results and the accuracy of the neural network forecasting is conducted.
У статті розглядається проблема створення гібридних інформаційно-аналітичних систем для фінансових ринків, що здатні працювати в режимі реального часу. Запропоновано архітектуру веб-орієнтованого додатку, яка інтегрує класичні моделі стохастичного числення (геометричний броунівський рух та модель Васічека) з алгоритмами глибинного навчання (рекурентні нейронні мережі LSTM). Описано математичний апарат, чисельні методи дискретизації (схема Ейлера-Маруями) та генерації ринкового шуму (перетворення Бокса-Мюллера). Обґрунтовано вибір стеку технологій (React.js, WebSocket) та алгоритмів управління потоковими даними (вікно ковзання). Проведено аналіз отриманих результатів симуляції та точності нейромережевого прогнозування.
Keywords: stochastic differential equations; Vasicek model; geometric Brownian motion; LSTM; machine learning; financial forecasting